RoboCup 2009: Robot Soccer World Cup XIII - Baltes, Jacky; Lagoudakis, Michail G.; Naruse, Tadashi; Ghidary, Saeed Shiry; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book includes the thoroughly refereed post-conference proceedings of the 13th RoboCup International Symposium, held in Graz, Austria, in June/July, 2009 - representing the core meeting for presentation and discussion of scientific contributions to a variety of research areas related to all RoboCup divisions (RoboCupSoccer, RoboCupRescue, RoboCup@Home, and RoboCupJunior). The 22 revised full papers and 17 revised poster papers presented were carefully reviewed and selected from 112 submissions. The contributions provide a valuable source of references and inspiration for R&D professionals interested in robotics and artificial intelligence.
Coordinated Action in a Heterogeneous Rescue Team -- Concept Evaluation of a Reflex Inspired Ball Handling Device for Autonomous Soccer Robots -- Development of a Realistic Simulator for Robotic Intelligent Wheelchairs in a Hospital Environment -- Creating Photo Maps with an Aerial Vehicle in USARsim -- Real-Time Hand Gesture Recognition for Human Robot Interaction -- Combining Key Frame Based Motion Design with Controlled Movement Execution -- Applying Dynamic Walking Control for Biped Robots -- Modeling Human Decision Making Using Extended Behavior Networks -- Motion Synthesis through Randomized Exploration on Submanifolds of Configuration Space -- Robust and Computationally Efficient Navigation in Domestic Environments -- Robust Collision Avoidance in Unknown Domestic Environments -- Real-Time Ball Tracking in a Semi-automated Foosball Table -- Three Humanoid Soccer Platforms: Comparison and Synthesis -- Learning Complementary Multiagent Behaviors: A Case Study -- Rollover as a Gait in Legged Autonomous Robots: A Systems Analysis -- Pareto-Optimal Collaborative Defensive Player Positioning in Simulated Soccer -- A Novel Camera Parameters Auto-adjusting Method Based on Image Entropy -- Object Recognition with Statistically Independent Features: A Model Inspired by the Primate Visual Cortex -- Using Genetic Algorithms for Real-Time Object Detection -- An Approximate Computation of the Dominant Region Diagram for the Real-Time Analysis of Group Behaviors -- A Lua-based Behavior Engine for Controlling the Humanoid Robot Nao -- Stable Mapping Using a Hyper Particle Filter -- A Characterization of 3D Sensors for Response Robots -- Multiple Model Kalman Filters: A Localization Technique for RoboCup Soccer -- Integrated Genetic Algorithmic and Fuzzy Logic Approach for Decision Making of Police Force Agents in Rescue Simulation Environment -- IntellWheels MMI: A Flexible Interface for an Intelligent Wheelchair -- Analyzing the Human-Robot Interaction Abilities of a General-Purpose Social Robot in Different Naturalistic Environments -- Communicating among Robots in the RoboCup Middle-Size League -- Multi-robot Cooperative Object Localization -- Evolution of Biped Walking Using Truncated Fourier Series and Particle Swarm Optimization -- Efficient Behavior Learning by Utilizing Estimated State Value of Self and Teammates -- Sensor and Information Fusion Applied to a Robotic Soccer Team -- Omnidirectional Walking Using ZMP and Preview Control for the NAO Humanoid Robot -- RoboCup@Home: Results in Benchmarking Domestic Service Robots -- Connecting the Real World with the Virtual World - Controlling AIBO through Second Life -- A Hybrid Agent Simulation System of Rescue Simulation and USARSim Simulations from Going to Fire-Escape Doors to Evacuation to Shelters -- SSL-Vision: The Shared Vision System for the RoboCup Small Size League -- Heuristic Formation Control in Multi-robot Systems Using Local Communication and Limited Identification -- Cooperative Multi-robot Map Merging Using Fast-SLAM.
Keywords: Engineering; Computer communication systems; Software engineering; User interfaces (Computer systems).; Artificial intelligence; Image processing; Control engineering; Engineering; Control; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Software Engineering; User Interfaces and Human Computer Interaction; Image Processing and Computer Vision; Electronic books